Impact of financial innovation and institutional quality on financial development in emerging markets - Suha Mahmoud Alawi; Wajih Abbassi; Rukhma Saqib; Madeeha Sharif (Journal of Risk and Financial Management, 2022)
Financial innovation and institutional quality play a key role in financial development. This study investigates the impact of financial innovation and institutional quality on financial development in an emerging markets setting. We used the sample of 17 emerging markets based on the availability of data from the period 1990-2020. Data were extracted from the World Development Indicator database. In this study, panel unit root, fully modified ordinary least squares and Pedroni Integration tests were applied to analyze the data. We find that financial innovation and institutional quality are significantly and positively related to financial development. Better financial innovation increases financial development, whereas low institutional quality in an emerging market can deteriorate financial development.
Keywords: 330; financial development; institutional quality; financial innovation; emerging markets